OPTIMALISASI MANAJEMEN PERPUSTAKAAN DALAM MENINGKATKAN BUDAYA LITERASI PESERTA DIDIK DI SMA MIFTAHUL ULUM JATIURIP - Siti Aisah; Irzak Yuliardy Nugroho; Sollah Solehudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
School libraries play a crucial role as a key supporting element in the learning process, particularly in building and developing reading interest and literacy habits among students. Optimally, these facilities go beyond mere book storage; they transform into integrated learning centers operated with a professional managerial approach. This approach encompasses essential stages such as strategic planning, effective resource management, structured daily activities, and continuous control and evaluation mechanisms to ensure high service quality. This study focuses on an in-depth analysis of the planning, implementation, and assessment stages of library management effectiveness in encouraging an increase in student literacy culture at SMA Miftahul Ulum Jatiurip, a pesantren-based educational institution. A qualitative approach with a case study design was chosen because of its ability to reveal the real picture and contextual nuances of library management practices in the school environment, which is unique due to the integration of religious values. Primary data were collected through in-depth interviews, direct field observations, and document studies, involving various key sources such as the principal, library management staff, supervising teachers, and students as the primary users. The data analysis process follows an interactive model that includes reducing raw information to essential patterns, presenting findings in a coherent narrative and visual form, and drawing inferences supported by strong evidence. This study aims to achieve a holistic understanding of the dynamics of library management at Miftahul Ulum Jatiurip High School, including a detailed understanding of key constraints such as budget or infrastructure limitations, as well as positive encouragement such as support from the Islamic boarding school community. This study is expected to summarize practical and theoretical values ​​in the development of library management in schools, especially in Islamic boarding school-based educational institutions. The findings obtained can be used as a primary reference for developing creative strategies to motivate students' interest in reading, for example through the integration of digital technology tools such as interactive e-book applications, strengthening literacy initiatives that collaboratively involve the Islamic boarding school community, and improving skills and training for library staff. As a result, the library is no longer just a supporting facility for the teaching and learning process, but is transformed into an effective center of change in building a sustainable literacy ecosystem, which is in line with the dynamics of the digital era and Islamic values ​​in the Islamic boarding school environment.